2007
DOI: 10.1016/j.bmcl.2007.04.092
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IGF-1R and lipoxygenase by nordihydroguaiaretic acid (NDGA) analogs

Abstract: Herein we pursue the hypothesis that the structure of nordihydroguaiaretic acid (NDGA) can be refined for selective potency against the insulin-like growth factor 1 receptor (IGF-1R) as a potential therapeutic target for breast cancer while diminishing its action against other cellular targets. Thus, a set of NDGA analogs (7a-7h) was prepared and examined for inhibitory potency against IGF-1R kinase and an alternative target, 15-lipoxygenase (15 LOX). The anti-cancer effects of these compounds were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…5B) and NDGA (7H) (supplemental Fig. 1A, available at www.jneurosci.org as supplemental material) (Blecha et al, 2007).…”
Section: Gaba B Receptor Activates Pi3 Kinase/akt Via G I/o -Proteinmentioning
confidence: 99%
“…5B) and NDGA (7H) (supplemental Fig. 1A, available at www.jneurosci.org as supplemental material) (Blecha et al, 2007).…”
Section: Gaba B Receptor Activates Pi3 Kinase/akt Via G I/o -Proteinmentioning
confidence: 99%
“…The lipoprotein-antioxidant activity of isolated 2 0 -hydroxy dihydroguaiaretic acid 7) and lipoxygenase inhibition of nordihydroguaiaretic acid (NDGA) have been reported. 8) However, the effect of stereochemistry has not been described. The oxidation enzyme-antioxidant activity of the enantiomers is compared in this report for the first time.…”
mentioning
confidence: 99%
“…1A), because it was reported that the inhibitory effect of NDGA on 15-LOX activity was shown to be modified by methylation of the hydroxyl group of its catechol ring (Blecha et al, 2007). The inhibitory effects of CBD, CBDM, and NDGA on 5/15-LOX-catalyzed oxygenation activity were examined using purified LOX as an enzyme source.…”
Section: Effects Of Cannabidiol and Its Derivative On Lox Activitymentioning
confidence: 99%
“…It has been reported that 15-LOX activity is quite sensitive to the structural modifications of the catechol ring of NDGA, an isomer of resorcinol (Fig. 1A), such as methylation of its hydroxyl group (Blecha et al, 2007), although NDGA is well known as a pan-LOX inhibitor (Hope et al, 1983;Whitman et al, 2002). There have been no reports investigating whether any cannabinoid(s) including CBD "selectively and potently" inhibit the 15-LOX isoform, whereas CBD having a resorcinol ring has been shown to inhibit LOX activity (Evans et al, 1987;Russo, 2004).…”
mentioning
confidence: 96%